Serendipitous learning: Recognizing and fostering the potential of microblogging - Ilona Buchem (Firenze University Press, 2013)
This paper introduces the concept of serendipitous learning in the context of microblogging and discusses the potential of unplanned and unexpected discoveries for learning. Serendipitous learning as a subset of incidental learning refers to learning through gaining new insights, discovering unrevealed aspects and recognizing seemingly unrelated connections. This type of learning can occur by chance and as a by-product of other activities like information browsing through social status updates in microblogs. It is argued that engaging in microblogging in an open social network of users frequently generating new information enhances the possibilities of serendipitous discovery. The paper discusses possible factors facilitating serendipitous learning and concludes with recommendations for future research.